1987
DOI: 10.1164/ajrccm/136.4.886
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of External Continuous Negative Pressure Ventilation Compared with Those of Continuous Positive Pressure Ventilation in Dogs with Acute Lung Injury

Abstract: Patients with noncardiogenic pulmonary edema requiring ventilatory assistance are usually supported with CPPV using positive end-expiratory pressure (PEEP), but CPPV requires endotracheal intubation and may decrease cardiac output (QT). The purpose of this study was to examine thoracoabdominal continuous negative pressure ventilation (CNPV) using external negative end-expiratory pressure (NEEP). The effects on gas exchange and hemodynamics were compared with those of CPPV with PEEP, with the premise that CNPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…This is because intrathoracic pressure is actually raised relative to body surface pressure, thereby reducing the gradient for venous return. It has been shown that this is not the case when the application of NPV is confined to the chest wall by using cuirass or jacket [39,40]. Unlike tank ventilators, these machines selectively decrease intrathoracic pressure so that right atrial pressure becomes more negative relative to the rest of the body, enhancing the gradient for venous return [40].…”
Section: Paediatric Diseasesmentioning
confidence: 99%
“…This is because intrathoracic pressure is actually raised relative to body surface pressure, thereby reducing the gradient for venous return. It has been shown that this is not the case when the application of NPV is confined to the chest wall by using cuirass or jacket [39,40]. Unlike tank ventilators, these machines selectively decrease intrathoracic pressure so that right atrial pressure becomes more negative relative to the rest of the body, enhancing the gradient for venous return [40].…”
Section: Paediatric Diseasesmentioning
confidence: 99%
“…Ventilation using a chest device (i.e., a cuirass or a jacket) causes hemodynamic effects that closely reflect spontaneous ventilation. However, ventilation with a total body device (e.g., a tank ventilator) results in hemodynamic effects that are comparable to those produced by the PPV; this is because of the loss of the driving pressure between the abdomen and the right atrium caused by the negative pressure applied to the abdominal surface (Lockhat et al 1992;Skaburskis et al 1987).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…This is because intrathoracic pressure is actually raised relative to body surface pressure, thereby reducing the gradient for venous return. SKABURSIS et al [49] and LOCKHAT et al [50] have shown that this is not the case when the application of NPV is confined to the thorax and upper abdomen by using cuirass or ponchowrap. Unlike tank ventilator, these machines selectively decrease intrathoracic pressure, so that right atrial pressure becomes more negative (relative to the rest of body), potentially enhancing the gradient for the venous return.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Unlike tank ventilator, these machines selectively decrease intrathoracic pressure, so that right atrial pressure becomes more negative (relative to the rest of body), potentially enhancing the gradient for the venous return. SKABURSIS et al [49] compared the effects of NPV plus negative end-expiratory pressure (NEEP) with PPV plus PEEP in six anaesthetized dogs with oleic acid induced pulmonary oedema. The two ventilatory modes were carefully matched for inspired oxygen fraction (FI,O 2 ), breathing frequency, tidal volume, and the increase in FRC.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
See 1 more Smart Citation